Pharmacological characterization of losartan as a CCR2 antagonist and pre-clinical and pharmacodynamic assessment as a potential anti-metastatic therapy - Regan, Daniel P., author; Dow, Steven, advisor; Schenkel, Alan, committee member; Thamm, Douglas, committee member; Slansky, Jill, committee member; Basaraba, Randall, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: CCL2; dogs; monocytes; CCR2; cancer; metastasis